Greenhouse Gases Produced During Forest Fires in the La Niña and El Niño Periods in South Sumatra Province - Hadiwijoyo, Erekso; Fata, Yulia Amirul; Saharjo, Bambang Hero (Jurnal Manajemen Hutan Tropika, 2025)
South Sumatra Province has characteristics that significantly increase hotspots and produce greenhouse gas (GHG) emissions in strong El Niño phenomena. This study investigates the impact of forest fires on GHG emissions during extreme climate in the South Sumatra Province from 2010 to 2020. This research analyzes the effects of La Niña and El Niño on the region by analyzing factors such as precipitation patterns, temperature fluctuations, hotspots, and greenhouse gas emissions. This study indicates that forest fires mostly happen during the dry season (May to October). El Niño occurred for the second time in 2015-2016 and 2018-2019, which affected the highest fire (hotspots, HSs) during the strong El Niño. Meanwhile, La Niña occurred three times in 2010-2011, 2011-2012, and 2017-2018, which is related to the low HSs found and represents the highest annual rainfall in the last ten years. The highest forest fire (HSs = 17.559) occurs in the characteristics of A1-B4 (precipitation 0-100, SSTA > 0.5°C). The highest GHG emission (>400 Mton) occurred in 2015 when the strong El Niño occurred in South Sumatra Province. The strong and weak El Niño produces the highest GHG emissions of more than 30 megatons per day, while the maximum mean daily GHG emission is under 10 megatons per day. Hotspot numbers rise exponentially with increasing SSTA, showing strong statistical relationships (R² > 0.80, r > 0.79) with burned area (R² = 0.90, r = 0.92) and burned area with CO₂ emissions (R² = 0.77, r = 0.79).